Analisis Perencanaan Struktur Kolom Dan Balok Pada Gedung Serbaguna Universitas Sains Cut Nyak Dhien - Darul Ambia; Yuslinda; Cut Meuthia Rani (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2026)
The Multipurpose Building of Cut Nyak Dhien University of Science, located at Jln. Perumnas No.45, Langsa Baro, Langsa City, Aceh, is classified as a Risk Category IV structure due to its function as a public facility. Based on this classification, the building is designed using Seismic Design Category C. The structural system employed is an Intermediate Moment Resisting Frame (IMRF), referring to applicable Indonesian building codes. Earthquake load analysis was conducted using the equivalent static analysis method based on SNI 1726:2012 concerning seismic resistance. All structural elements use reinforced concrete materials according to SNI 2847:2019, which outlines requirements for structural concrete. Structural analysis was performed using SAP2000 v.14 software.The analysis results for the main beam (B1) show support moment of -132.62 kN/m, mid-span moment of 83.52 kN/m, support shear force of -118.58 kN, and mid-span shear force of 110.63 kN. For the tie beam (RB), the support moment is -58.74 kN/m, mid-span moment 35.39 kN/m, support shear -44.62 kN, and mid-span shear 43.49 kN. The main column (K1) yields an axial force of -485.28 kN, bending moment of -76.77 kN/m, and shear force of 126.34 kN.The planned structural dimensions are as follows: Main Beam (B1) measures 40 x 60 cm, with support flexural reinforcement of 13D19, mid-span reinforcement of 7D19, support shear reinforcement D10-100 mm, and mid-span shear reinforcement D10-150 mm. The Ring Beam (RB) measures 25 x 40 cm with support reinforcement of 10D19, mid-span reinforcement of 6D19, support shear D10-75 mm, and mid-span shear D10-100 mm. Meanwhile, the main column (K1) has dimensions of 50 x 50 cm, using 14D19 flexural reinforcement and D10-150 mm shear reinforcement.